The Impact of Human Microbiotas in Hematopoietic Stem Cell and Organ Transplantation - Sen, Tirthankar; Thummer, Rajkumar P. (Frontiers in Immunology, 2022)
The human microbiota heavily influences most vital aspects of human physiology including organ transplantation outcomes and transplant rejection risk. A variety of organ transplantation scenarios such as kidney, lungs, liver and heart transplantation as well as hematopoietic stem cell transplantation is heavily influenced by the human microbiotas. The human microbiota refers to a rich, diverse, and complex ecosystem of bacteria, fungi, archaea, helminths, protozoans, parasites, and viruses. Research accumulating over the past decade has established the existence of complex cross-species, cross-kingdom interactions between the residents of the various human microbiotas and the human body. Since the gut microbiota is the densest, most popular, and most studied human microbiota, the impact of other human microbiotas such as the oral, lung, urinary, and genital microbiotas, are often overshadowed. However, these microbiotas provide critical and unique insights pertaining to transplantation success, rejection risk, and overall host health, across multiple different transplantation scenarios. Organ transplantation as well as the pre-, peri-, post-transplant pharmacological regimens patients undergo, and known to adversely impact the microbiotas, thereby increasing the risk of adverse patient outcomes. Over the past decade, holistic approaches to post-transplant patient care such as the administration of clinical and dietary interventions aiming at restoring deranged microbiota community structures has been gaining momentum. Examples of these include prebiotic and probiotic administration, fecal microbial transplantation, and bacteriophage-mediated multi-drug resistant bacterial decolonization. This review will discuss these perspectives and explore the role of different human microbiotas in the context of various transplantation scenarios.